Unveiling the Impact of Leadership on Community Engagement in Cicadas Village - Syahrir; Abd. Kadir, Iriyani (SCIENTIA: Journal of Multi Disciplinary Science, 2024)
This study aims to investigate the impact of village government leadership on enhancing community participation in development planning in Cicadas Village, Bogor Regency. The research utilized a quantitative method with a population of 234 households. Sampling was conducted through incidental sampling using the Slovin Formula, resulting in a sample size of 148 households. Data collection involved observation, questionnaires, and documentation. Data analysis employed frequency tabulation and simple regression analysis using IBM SPSS 23.0 for Windows. The findings indicate that village government leadership significantly influences community participation in development planning in Cicadas Village, evidenced by a calculated t-value of 8.778 and a significance value of 0.000 < 0.05, thus rejecting Ho and accepting Hi. Consequently, there exists a strong correlation between village government leadership and the optimization of community participation in development planning. Better village government leadership correlates with increased community participation in development planning. This research is expected to serve as a guideline for village governments in rural development planning and to provide comprehensive insights into the importance of village government leadership and community participation optimization.